Educational Leadership: Teacher Leadership Improves Student's Spiritual Intelligence - Poniman; Susanto; Ayu Andriyaningsih; Taridi; Emilia Putri Lestari (Journal of Education, Religious, and Instructions (JoERI), 2023)
This research focuses on the teacher's leadership role in increasing students' spiritual intelligence. In the era of modern education characterized by increasingly complex challenges and problems, raising students' spiritual intelligence becomes essential. This study uses a quantitative approach by taking samples from school teachers in Bandar Lampung. The results showed that teacher leadership significantly influenced increasing students' spiritual intelligence, with a t-value of 7.112 and a significance level of 0.00. In addition, the regression analysis shows that the teacher's leadership variable can explain 65.3% of the variability in increasing students' spiritual intelligence. These findings demonstrate the importance of the teacher's role as a leader in education to develop students' spiritual intelligence. Furthermore, this study emphasizes the need for training and professional development for teachers to consider and incorporate spiritual aspects into their educational approach.